Results of the first‐in‐human, randomized, double‐blind, placebo‐controlled phase 1b study of lumbar intrathecal bolus administrations of antisense oligonucleotide (ISIS 814907; BIIB080) targeting tau mRNA in patients with mild Alzheimer's disease. (31st December 2021) - Mummery, Catherine J; Junge, Candice; Kordasiewicz, Holly B; Mignon, Laurence; Moore, Katrina M; Yun, Chris; Baumann, Tiffany L; Li, Dan; Norris, Daniel A; Crean, Rebecca; Graham, Danielle; Huang, Ellen; et al.
Abstract: Background: ISIS 814907 (BIIB080) is an antisense oligonucleotide (ASO) that hybridizes to a complementary nucleotide sequence of mRNA of the human microtubule‐associated protein tau ( MAPT ) gene, preventing production of tau protein. Accumulation of hyperphosphorylated tau is associated with cognitive decline and brain atrophy in Alzheimer's Disease (AD). The placebo controlled period of the Phase 1b multiple ascending dose (MAD) study of ISIS 814907 in patients with mild AD is complete and the open‐label long term extension (LTE) is ongoing in the UK, Canada, Germany, Sweden, Netherlands and Finland (EudraCT: 2016‐002713‐22; NCT03186989). Methods: The study is divided into 2 parts. Part 1 is the MAD study, comprising a 3‐month Treatment Evaluation (TE) Period and a 6‐month Post‐Treatment (PT) Period. Part 2 is the open‐label LTE, comprising a 12‐month TE Period and a 4‐ or 6‐month PT Period. Four ascending dose cohorts were enrolled sequentially and randomized 3:1 to intrathecal (IT) bolus administrations of ISIS 814907 or placebo. Male or female patients aged 50‐74 years with mild AD and confirmed amyloid positivity (via CSF) at Screening were considered eligible. The primary objective was to assess safety and tolerability of multiple IT bolus administrations of ISIS 814907. The secondary objective was to evaluate CSF pharmacokinetics (PK). Exploratory objectives include assessment of plasma PK, target engagement and disease biomarkers, genotype and clinical endpoints relevant to AD. Results: All subjects (N=46) completed the MAD TE Period and 43 subjects completed the PT Period. All AEs were mild/moderate in severity. No serious AEs occurred in subjects receiving ISIS 814907. Dose‐dependent mean reduction from baseline in CSF total tau and phospho‐tau was observed in the TE period and continued in the PT period. CSF total tau and phospho‐tau reductions were comparable. Conclusions: IT bolus administration of multiple ascending doses of ISIS 814907 over 3 months was well‐tolerated in patients with mild AD. The robust lowering of CSF total tau and phospho‐tau warrants further investigation for the treatment of AD.